PHYSICO-CHEMICAL CONDITIONS OF VENT FAUNA FOSSILIZATION IN THE VMS DEPOSITS OF THE URALS AND PONTIDES: FLUID INCLUSION DATA - N.N. Ankusheva; V.V. Maslennikov; N.P. Safina (Минералогия)
Fluid inclusions in quartz, barite and calcite from fossilized fauna of hydrothermal massive and clastic ores from the deposits of the Urals (Valentorka, Saf’yanovka, Yubileynoe, Molodezhnoe, Shemur) and Pontides (Killik, Kyzylkaya) are studied with microthermometry, Raman spectroscopy and gas chromatography. Quartz from hydrothermal fauna was formed from NaCl and NaCl-KCl fluids with salinity up to 5–10 wt. % NaCl-equiv. and homogenization temperatures (Тhom) varying from 100 to 180 °C. Calcite from fauna was formed from the fluids with higher Тhom (200–250 °C) and lower salinity (3.5–7 wt. % NaCl-equiv.). Fluid inclusions in barite from fauna in clastic ores are characterized by variable salinity from 0.7–2 wt. % to 6–7 wt. % NaCl-equiv. (max 11 wt. %) and low to moderate Тhom (100–200 °C). Quartz of fauna from banded ores was formed from medium-temperature (Тhom 120–180 °C) NaCl-KCl fluids with salinity of 5–9 wt. % NaCl-equiv. According to gas chromatography and Raman spectroscopy, the fluids contain variable amounts of CO2 , CH4 and N2.